Commercial Release of Genetically Modified Crops in Africa: Interface Between Biosafety Regulatory Systems and Varietal Release Systems - Akinbo, Olalekan; Obukosia, Silas; Ouedraogo, Jeremy; Sinebo, Woldeyesus; Savadogo, Moussa; Timpo, Samuel; Mbabazi, Ruth; Maredia, Karim; Makinde, Diran; Ambali, Aggrey (Frontiers in Plant Science, 2021)
Commercial release of genetically modified (GM) crops for cultivation requires approval of the biosafety regulatory packages. The evaluation and approval of lead events falls under the jurisdiction of competent National Authorities for biosafety (which may be Ministries or autonomous Authorities or Agencies). The evaluation of lead events fundamentally comprises review of environmental, food and feed safety data as provided for in the Biosafety Acts and implementing regulations and, in some cases, in other relevant legal instruments. Although the lead GMO event may be commercially released for farmers’ cultivation, often, it is introgressed into locally adapted farmer preferred non-GMO cultivars which are already released and grown by the farmers. The introduction of new biotechnology products to the farmer is a process that includes comprehensive testing in the laboratory, greenhouse, and field over a period of time. The process provides answers to questions about the safety of the products before being introduced into the environment and marketplace. This is the first step in regulatory approvals. The output of the research and development phase of the product development cycle is identification of a safe and best-performing event for advancement to regulatory testing and likely commercialization and general release. The process of commercial release of new crop varieties in countries with established formal seed systems is guided by well-defined procedures and approval systems as regulated by the Seed Acts and implementing regulations. In countries with Seed laws, no crop varieties are approved for commercial cultivation prior to fulfilment of the National Performance Trials (NPTs) and Distinctness, Uniformity, Stability (DUS) tests and approval by the National Variety Release committee (NVRC). Against the backdrop of the preceding scenario, and for effective and efficient commercial release of GM crops for cultivation by farmers, while ensuring food and environmental safety, there is a need for close collaboration and interplay between the biosafety competent authorities and the variety release authorities. This paper outlines key challenges facing African countries in the deployment of GM crops, cites lessons learnt and best practices from countries that have successfully commercialized genetically engineered crops.